GROWTH and YIELD RESPONSE of TOMATO (Lycopersicum esculentum Mill.) on VERMICOMPOST FERTILIZATION and WATER SHOOTS PRUNING - Nur Aulia Suwari; Tuti Setyaningrum; Heti Herastuti (Techno LPPM, 2023)
Inorganic fertilizers used continuously in tomato cultivation cause soil degradation which will affect the growth and yield of tomato plants. Efforts to maintain soil fertility include applying organic fertilizers and reducing inorganic fertilizers, one of which is vermicompost. The aim of the study was to obtain the best treatment combination from the administration of various doses of vermicompost and the time of pruning water shoots. The research was conducted from July to October 2022 in Kalasan, Yogyakarta. The research method was a field experiment using a factorial Complete Randomized Block Design. Factor I was the dosage of vermicompost: 5 tons/ha, 10 tons/ha, 15 tons/ha, and 20 tons/ha. Factor II was the time of pruning water shoots: 20 days after planting (DAP), 35 DAP and 50 DAP. The results showed that vermicompost 20 tons/ha by pruning water shoots at 20 DAP gave the best results on the number and weight of fruit per plant. The treatment of vermicompost at 20 tons/ha gave the best results on plant height and stem diameter, as well as pruning water shoots at 20 DAP.